Peningkatan Hasil Belajar IPAS Menggunakan Model Problem Based Learning Berbantuan Media PPT Interaktif di Sekolah Dasar - Insani, Faradilla; Arwin, Arwin (Universitas Negeri Padang, 2025)
TThis research was conducted because the learning outcomes of students were not optimal. This study aims to describe the application of the Problem Based Learning model assisted by interactive PPT media to improve student learning outcomes in science learning for class IV SDN 1 Padang Panjang Timur. This type of research is Classroom Action Research with a qualitative and quantitative approach. The subjects of this study were 20 class IV students of SDN 1 Padang Panjang Timur in the 2024/2025 academic year. The results of the study showed an increase from cycle I to cycle II, namely: 1) The use of teaching modules in cycle I obtained 89.6% (B), increasing to 95.8% (A) in cycle II; 2) Implementation of learning from the teacher aspect in cycle I in the teacher aspect 87.4% (B), to 92.8% (A) in cycle II. While the increase that occurred in the student aspect in cycle I was 89.3% (B), to 96.4% (A) in cycle II; 3) Student learning outcomes can be seen from the average learning outcomes in cycle I which was 78.18% (C), becoming 93.56% (A) in cycle II.